Surface contamination of impervious areas on biogas plants and conclusions for an improved stormwater management. (20th April 2019) - Cramer, Michael; Rinas, Martin; Kotzbauer, Ulrich; Tränckner, Jens
Abstract: Biogas plants are an important technology for the intended shift towards energy production from renewable resources. But the handling of biomass in open silo facilities can create heavily polluted stormwater with severe impacts on the environment if discharged directly. The purpose of this study on a biogas plant in North-East Germany is to i) identify the main pollution sources, ii) quantify the surface specific pollution potential and iii) derive consequences to mitigate the environmental impact of stormwater from biogas plants. Two main pollution sources were identified: i) silage effluent, mainly occurring on the silo surfaces and ii) substrate losses along the transport paths. The surface specific pollution potential of COD, N and P was measured for characteristic subareas applying wet vacuum cleaning. The accumulation of pollution on the cover foil was very low, whereas the range of daily accumulation on the actively operated surface varied between 8.3 and 41.7 gCOD /(m 2 ·d). The pollution built-up is a highly stochastic process influenced by many factors (handled substrate, operational practice, meteorological conditions). Daily sweeping can significantly reduce the pollution potential for stormwater but cannot avoid the requirement of treatment prior to a discharge into a surface water. Graphical abstract: Image 10329 Highlights: Highly contaminated stormwater-runoff from silo facilities have an significant impact to the environmental. Surface built-up of contaminants on silo surfaces lead to heavily polluted stormwater runoff. Build-up of pollution can be modelled with a linear function. Sewage management of silage effluent and contaminated stormwater-runoff of silos are discussed. Recommendation of a intelligent silo facilities management are given.